How to catch a leprechaun - Wallace, Adam; Elkerton, Andy (Naperville, Illinois : Sourcebooks Jabberwocky, 2016)
A rhyming tale of St. Patrick's Day approaching and a leprechaun causing mischief while avoiding being caught in a trap.
Ages 4 and up.
Keywords: Stories in rhyme; Leprechauns -- Fiction; Saint Patrick's Day -- Fiction